MORPHOLOGICAL EFFECTS OF VACUUM-ASSISTED THERAPY ON EXPERIMENTAL PULMONARY ABSCESSES IN A DIABETIC RABBIT MODEL - Khamdamov, Sh.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Background: Pulmonary abscesses in diabetic individuals are often characterized by delayed inflammatory resolution and impaired healing. While vacuum-assisted closure (VAC) therapy is widely used in external wound management, its effects on internal thoracic infections remain insufficiently studied at the tissue level. Objective: To evaluate the histomorphological effects of VAC therapy on pulmonary abscesses in an experimental rabbit model with type 2 diabetes mellitus. Materials and Methods: A controlled animal study was conducted on 36 adult rabbits, divided into three groups: Group 1 (control, no VAC), Group 2 (continuous negative pressure - 80 mmHg), and Group 3 (intermittent pressure -80/0 mmHg, 5/2 cycle). Pulmonary abscesses were induced via transbronchial inoculation with S. aureus under general anesthesia. All animals had previously induced type 2 diabetes using streptozotocin. Histological samples were taken on days 3, 7, and 14 to evaluate inflammation, necrosis, granulation, vascularization, and collagen formation. Results: Rabbits in Group 2 showed accelerated granulation tissue formation, reduced necrotic area, and active fibroblast proliferation by day 7. Group 3 showed similar trends but less pronounced. The control group demonstrated persistent inflammation and poor cavity organization. By day 14, continuous VAC led to near-complete epithelialization of the cavity margins and dense neocollagen deposition. Intermittent VAC resulted in slower dynamics, while no-VAC animals retained abscess cavities with inflammatory infiltration. Conclusion: VAC therapy exerts favorable histomorphological effects in pulmonary abscess healing under diabetic conditions. Continuous negative pressure provided superior outcomes compared to intermittent mode. These findings support the biological rationale for applying VAC in thoracic infections, especially in compromised metabolic states.